Political legitimacy in Asia new leadership challenges - Kane, John; Loy, Hui-Chieh; Patapan, Haig (Palgrave series on Asian governance, 2011)
The editors of this collection bring together scholars of comparative politics, political philosophy and democratic theory to investigate the vital transformative role of dissident democratic leaders in Asia. It also examines the way leaders conduct themselves democratically in the course of their struggle and how they respond to demands to maintain democratic dissent once they succeed.